A PROJECT JURNAL THIRD WAVE FEMINISM IN BEYONCE KNOWLES’S “RUN THE WORLD (GIRLS)” - Sumamburat, Damayanti (LANTERN (Journal on English Language, Culture and Literature), 2017)
In this extended essay, the writer is interested in doing research by analyzing the music of American R & B singer, Beyonce Knowles entitling “Run The World (Girls)”. The writer chose this song because the writer sees that, the song emphasizes on actions the girls can carry on the song contains the struggle of the girls to reign the world. The girls color the society with their ability. In the daily life, girls become the one common topic which is often discussed. The purpose of writing this extended essay is to know more the meaning of the song lyric in several aspects, such as self-actualization, education, social status and others. Moreover, this extended essay is to figure out the society and feminism through the lyric.